Measuring ego-centered social networks: do cheaper methods with low respondent burden provide good estimates of network composition? - Kogovšek, Tina (Metodološki zvezki, 2008)
In measuring ego-centered social networks, two general approaches can be distinguished. A very simple way to evaluate membership in a social network is to ask an ordinary survey question where response categories are types of relationships (e.g. partner, parents, children, friends, etc.). This approach is very appealing as it saves time and money. However, information obtained by this approach is very limited. Most often, when evaluating ego-centered networks, the name generator approach is used. The list of egos (respondents) is obtained in the first step. In the second step, existing ties are identified - all alters with whom the focal ego has some sort of relationship. When all ties have been identified, the contents and the characteristics of ties are assessed. In most cases the characteristics of the alters are also measured. The name generator approach yields more data and is also of higher quality. However, it is very time and money consuming, and it requires either considerable effort from respondents, when it is applied inself-administered mode, or complex coordination between interviewer and respondent, when it is applied in personal interviews (e.g. Kogovšek et al., 2002). In a series of studies, network composition was estimated using both approaches. Test-retest and split-ballot experiments on convenience samples of respondents were used to assess the stability of network composition. Findings are discussed with regard to survey complexity, respondent burden, costs and quality of network composition estimates.
Keywords: Measurement; Merjenje; Social networks; Družbena omrežja; Družboslovne ankete; Social surveys; Stroški; Costs; družboslovno raziskovanje; analiza omrežij